Impact of Control Constraint on A Multi-Objective Buck Converter Design - Cherif Larouci; Kamal Ejjabraoui; Pierre Lefranc; Claude Marchand (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
The current paper deals with a multi-objective design approach of power converters applied to a DC-DC buck structure. This approch consists on optimizing a preselected power architecture by minimizing a multi-objective function (volume and time response) under multi-physic constraints (efficiency, thermal, electromagnetic compatibility and control). This multi-objective optimization allows evaluating the impact of the control aspect on the converter design by considering the control criteria with the same importance as the conventional constraints. The obtained results confirm the influence of the control on the converter design parameters. They help the designer to choose suitable operating points depending on the desired performances in terms of volume and time response while respecting efficiency, junction temperatures and electromagnetic compatibility constraints.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.369